Nutritional Interventions Improved Rumen Functions and Promoted Compensatory Growth of Growth-Retarded Yaks as Revealed by Integrated Transcripts and Microbiome Analyses - Hu, Rui; Zou, Huawei; Wang, Zhisheng; Cao, Binghai; Peng, Quanhui; Jing, Xiaoping; Wang, Yixin; Shao, Yaqun; Pei, Zhaoxi; Zhang, Xiangfei; Xue, Bai; Wang, Lizhi; et al. (Frontiers in Microbiology, 2019)
Growth retardation reduces the incomes of livestock farming. However, effective nutritional interventions to promote compensatory growth and the mechanisms involving digestive tract microbiomes and transcripts have yet to be elucidated. In this study, Qinghai plateau yaks, which frequently suffer from growth retardation due to malnutrition, were used as an experimental model. Young growth-retarded yaks were pastured (GRP), fed basal ration (GRB), fed basal ration addition cysteamine hydrochloride (CSH) (GRBC) or active dry yeast (ADY) (GRBY), Another group of growth normal yak was pastured as a positive control (GNP). After 60-day nutritional interventions, the results showed that the average daily gain (ADG) of GRB was similar to the level of GNP, and the growth rates of GRBC and GRBY were significantly higher than the level of GNP (P < 0.05). Basal rations addition of CSH or ADY either improved the serum biochemical indexes, decreased serum LPS concentration, facilitated ruminal epithelium development and volatile fatty acids (VFA) fermentation of growth-retarded yaks. Comparative transcriptome in rumen epithelium between growth-retarded and normal yaks identified the differentially expressed genes mainly enriched in immune system, digestive system, extracellular matrix and cell adhesion pathways. CSH addition and ADY addition in basal rations upregulated ruminal VFA absorption (SLC26A3, PAT1, MCT1) and cell junction (CLDN1, CDH1, OCLN) gene expression, and downregulated complement system (C2, C7) gene expression in the growth-retarded yaks. 16S rDNA results showed that CSH addition and ADY addition in basal rations increased the rumen beneficial bacterial populations (Prevotella_1, Butyrivibrio_2, Fibrobacter) of growth-retarded yaks. The correlation analysis identified that ruminal VFAs and beneficial bacteria abundance were significantly positively correlated with cell junction and VFA absorption gene expressions and negatively correlated with complement system gene expressions on the ruminal epithelium. Therefore, CSH addition and ADY addition in basal rations promoted rumen health and body growth of growth-retarded yaks, of which basal ration addition of ADY had the optimal growth-promoting effects. These results suggested that improving nutrition and probiotics addition is a more effective method to improve growth retardation caused by gastrointestinal function deficiencies.